Effectiveness of Science Learning Using Physics Kit Media on Conceptual Understanding - Susanti, Susanti; Ernawati, Tias; Septiani, Devi (Prodi Pendidikan Fisika Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine the effectiveness of using Physics Kit media in improving conceptual understanding in physics. The research was conducted during the 2023/2024 academic year. This study is a quasi-experimental research. Data were collected using test instruments. The subjects of the study were 21 students from the Science Education program. The data analysis technique used was N-Gain. The results indicate that learning using Physics Kit media is effective in enhancing students' conceptual understanding in physics. The N-Gain percentage of 86.33% falls into the high category, with an effective interpretation.